2008
DOI: 10.7202/018005ar
|View full text |Cite
|
Sign up to set email alerts
|

Les taux de suicide des jeunes hommes québécois : facteurs de risques et de protection

Abstract: Des indicateurs socioprofessionnels, familiaux et scolaires ont été mis en relation avec les taux de suicide des jeunes hommes et femmes de 15-19 ans et 20-24 ans pour la période 1979-1999. Des corrélations significatives montrent que la croissance des taux est reliée positivement pour les adolescents de 15-19 ans à l’augmentation des taux de divorce et de familles monoparentales et que les taux de suicide sont négativement reliés aux taux d’activité. Plusieurs indicateurs scolaires montrent également des rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
1
1
1
Order By: Relevance
“…Analyses on the crude effect of the law comparing the mean total suicide rates between the two periods showed a significant increase in TSR after the law was implemented. Contrary to Stack's (2000a) conclusion for unemployment and to the conclusion of Stack (2000b) and Caron and Robitaille (2007) for divorce, unemployment and divorce rates were not related to the upward trend in suicide rate in Quebec during this period. Our results were consistent with those of Leenaars et al (2003) for suicide rates in Canada in the period from 1969 to 1985.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Analyses on the crude effect of the law comparing the mean total suicide rates between the two periods showed a significant increase in TSR after the law was implemented. Contrary to Stack's (2000a) conclusion for unemployment and to the conclusion of Stack (2000b) and Caron and Robitaille (2007) for divorce, unemployment and divorce rates were not related to the upward trend in suicide rate in Quebec during this period. Our results were consistent with those of Leenaars et al (2003) for suicide rates in Canada in the period from 1969 to 1985.…”
Section: Discussioncontrasting
confidence: 91%
“…Stack (2000b), in a review of the literature, showed that nearly 80% of study results converged to demonstrate a positive association between divorce and suicide. Moreover, Caron and Robitaille (2007), using multiple regressions including a number of social variables, reported a strong association between divorce rates and suicide rates among young Quebeckers under the age of 25 in the period from 1979 to 1999, but found no such association with unemployment rates.…”
mentioning
confidence: 97%
“…À ce chapitre, le taux de chômage était, en 2006, à son plus faible niveau des 30 dernières années (Legris, 2007). Malgré ce contexte, les résultats d'analyses réalisées sur des données québécoises suggèrent que les taux de décès par suicide des adolescents et des jeunes adultes ne sont pas associés aux taux de chômage de ces groupes, tant chez les hommes que chez les femmes (Caron et Robitaille, 2007). (Potvin, 2004).…”
Section: Point De Jonctionunclassified